The teacher's sense of plausibility - Alan Maley (Peoples' Friendship University of Russia (RUDN University), 2018)
Dr Neiman Stern Prabhu is one of the pioneers in the development of task-based learning and the communicative teaching of language through his work on the Bangalore Project in India in the late 1960s and early 1970s. The work he instituted as part of the project has since become one of the bases of current language learning theory and practice. However, the teaching of language methodology through teacher training courses does not necessarily ensure it will be taken up and used by all teachers. Far more important in Prabhu's view is teachers' own 'sense of plausibility', which is based on experience and which determines how they think about language and how language is best learned. This often-unconscious process of reflection informs teachers' personal psychology and influences what teaching and learning approaches they find plausible and therefore acceptable. The paper aims to explore Prabhu's contributions to language learning and teaching through the development of task-based learning and the communicational approach, examine his concept of 'the teacher's sense of plausibility', and give it substance by applying it, as an example, to the author's own career. It emphasises how teachers develop professionally (and personally) by building a personal theory of teaching action based upon their own accumulated experiences - and reflection on them. In doing so, the article suggests that the continuing development of a personal 'theory' of teaching can be a valuable element within the framework of teacher development as a whole.